ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH, BUDAYA ORGANISASI, KOMPETENSI TERHADAP KEPUASAN KERJA GURU SLB DI KABUPATEN ACEH BARAT - Yusnaidi Yusnaidi; Hera Yanti; Said Mulyadi (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
The objectives of this research are (1) To determine the influence of the Principal's Leadership Style on the Job Satisfaction of Special School Teachers in West Aceh Regency. (2) To determine the influence of Organizational Culture on SLB Teacher Job Satisfaction in West Aceh Regency. (3) To determine the influence of Competency on the Job Satisfaction of Special School Teachers in West Aceh Regency, and (4) To determine the influence of Principal Leadership Style, Organizational Culture and Competency on the Job Satisfaction of Special School Teachers in West Aceh Regency. This research uses a quantitative method with a descriptive approach, a population of 36 people, a sample of 36 people, a simple random sampling technique using Sugiyono's sampling technique. The data collection technique was carried out using a Likert scale questionnaire and multiple linear regression data processing techniques. The research findings were partially obtained, (1) the school principal's leadership style did not have a positive influence on teacher job satisfaction with a coefficient of 0.484 or 48.4% (in percentage), hypothesis testing produced a calculated T value of 0.708 which was smaller than the T table value 1,690. This shows that the principal's leadership style variable has no effect on teacher job satisfaction. (2) organizational culture does not have a positive influence on teacher job satisfaction with a coefficient of 0.683 or 68.3% (in percentage). Hypothesis testing produces a calculated T value of 0.412 which is smaller than the T table value of 1.690. This shows that organizational culture variables have no effect on teacher job satisfaction. (3) Competency has a positive influence on teacher job satisfaction with a coefficient of 0.049 or 4.9% (in percentage). Hypothesis testing produces a calculated T value of 2.007 which is greater than the T table value of 1.690. This shows that the competency variable influences teacher job satisfaction. Meanwhile, simultaneously it was found that the principal's leadership style, organizational culture and competence had a positive influence on teacher job satisfaction with a constant value of 27,670. The findings in this research have practical implications, namely the principal's leadership style, organizational culture and competence have implications for teacher job satisfaction. Advice to all school principals is that the implementation of the principal's leadership style should be given more attention and carried out with full responsibility, and the output is to realize teacher job satisfaction, organizational culture also needs to be implemented as well as possible, so that a comfortable and conducive atmosphere will be created in carrying out activities organization and the realization of teacher job satisfaction, teachers are required to have adequate competence as per existing provisions, so that the target of improving the quality of learning can be achieved well, and a teacher's job satisfaction must also be owned and maintained by every teacher so that they remain enthusiastic in carrying out their duties and responsibilities. responsibility as an educator so that it is hoped that this will have an impact on the job satisfaction of special school teachers in West Aceh Regency.